ANALISIS WILLINGNESS TO PAY DAN PENGARUH VARIABEL PENDAPATAN, JUMLAH TANGGUNGAN RUMAH TANGGA, USIA, AKSES KE SEKOLAH TERHADAP PEMILIHAN SERTA PENGEMBANGAN STRATEGI PENGELOLAAN SEKOLAH - Christina Whidya Utami; Metta Padmalia (Jurnal Bisnis dan Keuangan, 2021)
The purpose of this study is to estimate and analyze the willingness to pay and fax tor the factors that affect the willingness to pay at High School in the of Semarang. The method used is Contingent Valuation Method (CVM) and multiple linear regression analysis. The number of samples in this study were 238 respondents, the sampling technique was done by snowball sampling. The results of this study indicate that the average willingness to pay (WTP) of households in High Schools in Semarang is Rp.559.034,00. Factors that have a significant influence on WTP values are income variables, number of household dependents, age and length of access. Whereas the factors that have no effect on willingness to pay (WTP) are parents' education variables. Based on the results of the study, the suggestions that can be put forward are the management or the government to improve the quality of the Vocational School as well as the development of a transparency policy on the collection and allocation of user fees and other resources.